Continent-wide variation in feather colour of a migratory songbird in relation to body condition and moulting locality - Ryan Norris, D (The Royal Society, 2006)
Understanding the causes of variation in feather colour in free-living migratory birds has been challenging owing to our inability to track individuals during the moulting period when colours are acquired. Using stable-hydrogen isotopes to estimate moulting locality, we show that the carotenoid-based yellow–orange colour of American redstart (Setophaga ruticilla) tail feathers sampled on the wintering grounds in Central America and the Caribbean is related to the location where feathers were grown the previous season across North America. Males that moulted at southerly latitudes were more likely to grow yellowish feathers compared with males that moulted more orange–red feathers further north. Independent samples obtained on both the breeding and the wintering grounds showed that red chroma—an index of carotenoid content—was not related to the mean daily feather growth rate, suggesting that condition during moult did not influence feather colour. Thus, our results support the hypothesis that feather colour is influenced by ecological conditions at the locations where the birds moulted. We suggest that these colour signals may be influenced by geographical variation in diet related to the availability of carotenoids.